2002
DOI: 10.1063/1.1436274
|View full text |Cite|
|
Sign up to set email alerts
|

Organic bistable light-emitting devices

Abstract: An organic bistable device, with a unique trilayer structure consisting of organic/metal/organic sandwiched between two outmost metal electrodes, has been invented. ͓Y. Yang, L. P. Ma, and J. Liu, U.S. Patent Pending, U.S. 01/17206 ͑2001͔͒. When the device is biased with voltages beyond a critical value ͑for example 3 V͒, the device suddenly switches from a high-impedance state to a low-impedance state, with a difference in injection current of more than 6 orders of magnitude. When the device is switched to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 13 publications
1
40
1
Order By: Relevance
“…[11][12][13][14][15][16][17] Among the several types of nonvolatile memory devices, organic bistable devices ͑OBDs͒ have been particularly interesting and promising candidates for next-generation nonvolatile memory devices due to their relatively simple fabrication process without additional sources and drains. [18][19][20][21][22][23] Even though some investigations concerning the memory effects in OBDs fabricated utilizing inorganic nanoparticles embedded in an organic layer fabricated by using a precisely controlled method under vacuum conditions have been performed, 18-23 studies on the electrical bistabilities, the memory stabilities, and the memory mechanisms in OBDs made of synthesized ZnO quantum dots ͑QDs͒ blended with an insulating polymethylmethacrylate ͑PMMA͒ polymer fabricated by using a simple spin-coating method have not been reported yet.…”
Section: Electrical Bistabilities and Memory Mechanisms Of Organic Bimentioning
confidence: 97%
“…[11][12][13][14][15][16][17] Among the several types of nonvolatile memory devices, organic bistable devices ͑OBDs͒ have been particularly interesting and promising candidates for next-generation nonvolatile memory devices due to their relatively simple fabrication process without additional sources and drains. [18][19][20][21][22][23] Even though some investigations concerning the memory effects in OBDs fabricated utilizing inorganic nanoparticles embedded in an organic layer fabricated by using a precisely controlled method under vacuum conditions have been performed, 18-23 studies on the electrical bistabilities, the memory stabilities, and the memory mechanisms in OBDs made of synthesized ZnO quantum dots ͑QDs͒ blended with an insulating polymethylmethacrylate ͑PMMA͒ polymer fabricated by using a simple spin-coating method have not been reported yet.…”
Section: Electrical Bistabilities and Memory Mechanisms Of Organic Bimentioning
confidence: 97%
“…[11][12][13][14][15] Some works concerning the electrical properties and memory effects in OBDs fabricated utilizing inorganic nanoparticles embedded in the organic layer by using a precisely control method have been performed. [16][17][18][19][20] Studies concerning the electrical bistabilities and memory mechanisms of OBDs based on colloidal ZnO quantum dot ͑QD͒-polymethylmethacrylate ͑PMMA͒ polymer nanocomposites have been conducted. 21 ZnO QDs embedded in the PMMA layer act as carrier trap sites.…”
mentioning
confidence: 99%
“…Experimentally, it is found that OLEDs with high work function such as Au or Cu with specific amount of NPs (it depends on organic materials and fabrication process) can achieve nearly the same turn-on voltage and current density in comparison with low work function such as Ag. But in working voltage the differences are in low intensity and El for high work function OLEDs [25][26][27][28][29][30]. Indeed, it is believed that light scattering and light absorption of In NPs thin layer, decreases the efficiency of OLED [35].…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Since, the thickness of emissive layer was fixed so thickness variation did not have any broadening effect. A specific amount of metal nanostructure can enhance E-field effect [11,[25][26][27][28][29][30][31]. If the polymer molecules are in the vicinity of the metal NPs, the ground state to excited state transition probability can be increased.…”
Section: -Results and Discussionmentioning
confidence: 99%